2020
DOI: 10.3390/foods9111522
|View full text |Cite
|
Sign up to set email alerts
|

Compositional Features of the “Kweli” Red Raspberry and Its Antioxidant and Antimicrobial Activities

Abstract: Red raspberries (Rubus idaeus L.) are increasingly popular foods in contemporary diets due to their freshness, nutritional value and health claims. Among the existing cultivars, “Kweli” is one of the most productive and widely cultivated. In this study, the nutritional value and chemical composition of “Kweli” red raspberry were characterized by the official method of food analysis and chromatographic techniques, and its antioxidant and antimicrobial activities were tested against biological/biochemical oxidiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…Cyanidin-3-arabinoside (Rf = 0.18) was not found in tested extracts. Numerous anthocyanins have been identified in raspberry fruits, mainly cyanidin derivatives (sophoroside, glucoside, rutinoside as well as diglucosides) and pelargonidin [ 38 , 39 , 40 ]. Blackberries are also dominated by cyanidin glycosides [ 41 , 42 , 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cyanidin-3-arabinoside (Rf = 0.18) was not found in tested extracts. Numerous anthocyanins have been identified in raspberry fruits, mainly cyanidin derivatives (sophoroside, glucoside, rutinoside as well as diglucosides) and pelargonidin [ 38 , 39 , 40 ]. Blackberries are also dominated by cyanidin glycosides [ 41 , 42 , 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Despite the scarcity of studies reporting the presence of raffinose and trehalose in fruits, some authors have reported their presence in berries. For instance, Aksic et al [16] detected trehalose and raffinose in three blueberry cultivars ('Bluecrop', 'Duke', and 'Nui'), while Palonen et al [17] reported the presence of raffinose in 'Festival', 'Titan', and 'Willamette' raspberries, and Vara et al [18] of both raffinose and trehalose in 'Kwely' raspberries.…”
Section: Introductionmentioning
confidence: 99%
“…Although the bioavailability of both anthocyanins and ellagitannins is low and depends on several factors, such as the food matrix, dose and time of intake, interactions with gut microbiota as well as other polyphenols during digestion and absorption, there is increasing evidence that their biological activity may provide significant health benefits [13,20,21]. In addition to the bioactive compounds of RR there are post-ingestion metabolites such as short chain fatty acids that are shown to confer potential health benefits [22][23][24][25].…”
Section: Bioactive Compoundsmentioning
confidence: 99%
“…There is evidence that the benefits of dietary berries can be feasibly attained through daily consumption of 40-250 g of fresh, frozen, or dried berries, or their extracts [12]. Numerous health benefits have been documented from consuming RR and its bioactive constituents including improved glucose, insulin, and lipid metabolism, as well as antioxidant, anti-inflammatory and signaling properties which have the potential to reduce the risk for and modulate chronic metabolic diseases [12,23,24].…”
Section: Proposed Health Benefitsmentioning
confidence: 99%